G146(P) Is death a poor man's currency? A time-series analysis of resource use and outcomes in a paediatric intensive care unit. (27th April 2016) - Ray, S; Pierce, C; Brierley, J
Abstract : Aims: John Rawls' principle of 'maximin' – spending the maximum amount of resources on the proportion of society that is worst off has governed healthcare resource allocation in the U. K. However the principle fails when resources are scarce and the majority of the population is deprived of their needs. We hypothesise that in the context of life sustaining technology the focus on mortality as an outcome measure in both clinical practice and research may lead to the failure of the maximin principle. Paediatric intensive care is both an expensive and scarce resource. We aimed to examine the effect of resource use and outcome within a PICU to explore our hypothesis further. Methods: Time series analyses to investigate resource use (length of stay/bed days) and outcome in a single PICU between 2004 and 2014. Results: The number of deaths per month has decreased over the period. However both the median and mean length of stay values has increased. Moreover, the difference between the mean and the median has increased and is positive. This suggests that more bed days are being occupied by outliers in the lengths of stay (either more outliers or outliers staying longer). Children in top quartile for length of stay utilised an increasing number of bed days over the period, but there was also a trend towards an increase in the number of deaths in this sub-group. Conclusion: Our data suggests over the last decade the length of stay in PICU has increased. In particular though, children who eventually die are being kept alive for longer. They utilise a greater proportion of resources. Clinicians and researchers need to be cognisant that this does not affect access to healthcare resources for the majority of children.